SYSTEMATIC LITERATURE REVIEW: UPAYA PERPUSTAKAAN DI INDONESIA UNTUK MELAYANI PEMUSTAKA PENYANDANG DISABILITAS - Latifatur Rohmah; Roselind Oktovanie (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Libraries are institutions that provide services to users for various information needs. Service efforts for people with disabilities are the responsibility of each library unit. This research aims to examine the library’s efforts in serving people with disabilities in order to make a significant contribution and encourage libraries to continue to innovate and adapt in meeting the needs of all library users. This research uses the Systematic Literature Review (SLR) method, which analyzes and combines literature related to the research topic. The literature analyzed was indexed on Google Scholar and published between 2017 and 2021. The literature collected was selected based on the criteria set to match the research topic. There were five literatures analyzed in this research. The research results show that libraries in Indonesia have contributed to the development and improvement of special services for people with disabilities, especially through the provision of physical services, Braille corner services, and support from librarians.